Effectiveness of Dental Health Education with Media Videos on Instagram, Facebook and Youtube on Changes in Knowledge and Attitudes of the Public about the Importance of Dental Nerve Care - Variani, Ratih; Sidabutar, Manginar; Ayatullah, M. Ibraar (Dental Therapist Journal, 2023)
One way to improve behaviour is to provide dental health education using audio-visual media such as videos. Social media-based health education has been empirically proven to be effective in conducting health promotion efforts with the aim of increasing understanding and providing support to the community for healthy behaviour. Currently, Facebook, Instagram and YouTube are 3 of the 7 social media most accessed by Indonesians in 2023. The purpose of this study was to determine the effectiveness of dental health education with video media on Instagram, Facebook and YouTube on changes in public knowledge and attitudes about the importance of root canal treatment. This type of research is quasy-experimental without group controls, with a one group pretest-posttest design. The sample size was 60 people. Respondents filled out a google form link questionnaire that was distributed. The results showed that dental health education with videos on social media instagram, facebook and youtube was effective in changing people's knowledge and attitudes where the p value of the three social media was 0.000 where p < 0.005 (wilcoxon test). Different test of 3 social media with kruskal willis where the result is that there is no difference in effectiveness between the three social media (p value> 0.005). The conclusion of this study is that educational videos on social media Instagram, Facebook and YouTube are effective in changing people's knowledge and attitudes, but there is no difference in effectiveness between the three social media.   The results of this study can be a reference for using social media in dental health education so that it can be more accepted by the community. In the future, research can be developed with other types of social media and factors that affect the effectiveness of these media.